Vocabulary Learning Strategies and Vocabulary Size: A Correlational Study of Iraqi Undergraduate Students - Safa Yaseen Noori; Ala'a Ismael Challob (Universitas Pahlawan Tuanku Tambusai, 2026)
Understanding the relationship between English vocabulary learning strategies (VLSs) and vocabulary size (VS) represents a controversial issue among previous studies in the field of applied linguistics. Hence, the current study attempted to identify the (VLSs) and (VS) among Iraqi EFL university students. Besides, it examined the relationship between (VLSs) and (VS) among Iraqi EFL university students. A quantitative correlational research design was employed supported by the (VLSs) questionnaire, and (VS) test. The sample of study is represented by 258 EFL university students in their fourth year who were selected conveniently from the Dept. of English, College of Education for Humanities and College of Education for Women- University of Anbar throughout the first semester of the academic year 2025-2026. Data was analyzed quantitatively using SPSS to calculate means, standard deviations, t-test, Pearson’s Correlation, and multiple regression analysis. Findings indicated that Iraqi undergraduate students actively use various VLSs, particularly metacognitive, memory, and cognitive strategies, to mitigate their vocabulary knowledge. In addition, the findings revealed that there is a statistically positive and significant relationship between the effective use of the majority of VLSs and students’ VS, which in turn contributes to their overall language proficiency. The study concludes that mastering VLSs is essential for EFL students, particularly in the Iraqi context, were limited exposure to English poses challenges to vocabulary development. By adopting effective strategies, students do not only enlarge their VS but also enhance their communicative competence, academic performance, and lifelong learning skills.